Genotoxicological assessment of two reactive dyes extracted from cotton fibres using artificial sweat - Leme, Daniela Morais; de Oliveira, Gisele Augusto Rodrigues; Meireles, Gabriela; dos Santos, Tuane Cristina; Zanoni, Maria Valnice Boldrin [UNESP]; de Oliveira, Danielle Palma (Elsevier, 2013)
Human eyes have a remarkable ability to recognize hundreds of colour shades, which has stimulated the use of colorants, especially for clothing, but toxicological studies have shown that some textile dyes can be hazardous to human health. Under conditions of intense perspiration, dyes can migrate from coloured clothes and penetrate into human skin. Garments made from cotton fabrics are the most common clothing in tropical countries, due to their high temperatures. Aiming to identify safe textile dyes for dyeing cotton fabrics, the genotoxicity [in vitro Comet assay with normal human dermal fibroblasts (NHDF), Tail Intensity] and mutagenicity [Salmonella/microsome preincubation assay (30 min), tester strains TA98, TA100, YG1041 and YG1042] of Reactive Blue 2 (RB2, CAS No. 12236-82-7, C.I. 61211) and Reactive Green 19 (RG19, CAS No. 61931-49-5, C.I. 205075) were evaluated both in the formulated form and as extracted from cotton fibres using different artificial sweats. Both the dyes could migrate from cotton fibres to sweat solutions, the sweat composition and pH being important factors during this extraction. However, the dye sweat solutions showed no genotoxic/mutagenic effects, whereas a weak mutagenic potential was detected by the Ames test for both dyes in their formulated form. These findings emphasize the relevance of textile dyes assessment under conditions that more closely resemble human exposure, in order to recognize any hazard. © 2013 Elsevier Ltd. All rights reserved.
Keywords: CAS No. 12236-82-7/C.I. 61211; CAS No. 61931-49-5/C.I. 205075; Comet assay; Genotoxicity; In vitro; Salmonella/microsome assay (Ames test)